2013
DOI: 10.1111/pce.12184
|View full text |Cite
|
Sign up to set email alerts
|

Genetic variation in yield under hot ambient temperatures spotlights a role for cytokinin in protection of developing floral primordia

Abstract: Unusually hot ambient temperatures (HAT) can cause preanthesis abortion of flowers in many diverse species, limiting crop production. This limitation is becoming more substantial with climate change. Flower primordia of passion fruit (Passiflora edulis Sims) vines exposed to HAT summers, normally abort. Flower abortion can also be triggered by gibberellin application. We screened for, and identified a genotype capable of reaching anthesis during summer as well as controlled HAT conditions, and also more resist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
45
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(47 citation statements)
references
References 57 publications
1
45
0
1
Order By: Relevance
“…In rice, exogenous BAP application increased the abundance of tZ-type CTKs (Liu et al, 2011) and the number of spikelets per panicle (Ding et al, 2014). Similarly, several passion fruit species and Arabidopsis ecotypes that showed stable abundance of aCTKs had less severe reductions in floret number in comparison with species and ecotypes that showed reduced CTK abundance in response to high temperature when exogenous CTKs were applied to mitigate the effect of heat injury on floret growth (Sobol et al, 2014). Additionally, we observed that relative panicle CTK concentrations were positively correlated with the relative number of spikelets per panicle ( Figure 5A ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In rice, exogenous BAP application increased the abundance of tZ-type CTKs (Liu et al, 2011) and the number of spikelets per panicle (Ding et al, 2014). Similarly, several passion fruit species and Arabidopsis ecotypes that showed stable abundance of aCTKs had less severe reductions in floret number in comparison with species and ecotypes that showed reduced CTK abundance in response to high temperature when exogenous CTKs were applied to mitigate the effect of heat injury on floret growth (Sobol et al, 2014). Additionally, we observed that relative panicle CTK concentrations were positively correlated with the relative number of spikelets per panicle ( Figure 5A ).…”
Section: Discussionmentioning
confidence: 99%
“…In rice, Arabidopsis and passion fruit, reduced CTK abundance in shoots in response to heat caused floret abortion, whereas exogenous CTK application to shoots mitigated the effects of heat injury on branches and florets (Sobol et al, 2014; Wu et al, 2016). CTK transportation via xylem sap is involved in heat stress tolerance (Ha et al, 2012; Zwack and Rashotte, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Both exogenous application of CKs [10] and elevation of CK levels by overexpression of the biosynthetic gene isopentenyltransferase (ipt) under the senescence-inducible promoter (SAG12) resulted in elevation of HS tolerance [11]. Protective role of CKs on developing flowers exposed to HS was demonstrated [12]. Recently, CK induction of a high number of heat stress responsive proteins was reported in Arabidopsis [13].…”
Section: Introductionmentioning
confidence: 99%
“…Ahmadi and Fotokian [26] have indicated the linkage of markers RM251 and RM282 on rice chromosome 3 to potassium ion concertration. Lin et al ., [27] have shown linkage of RM112 and RM530 on chromosome 2 to leaf rolling in rice plants due to water stress. QTL mapping of rice indicated the linkage of rice grain and kernel length, breadth, length/breadth ratio kernel length after cooking and aroma to 18 different SSR markers [28,29].…”
Section: Introductionmentioning
confidence: 99%